Risk of Clot Formation in Femoral Arterial Sheaths Maintained Overnight for Neuroangiographic Procedures - Koenigsberg, Robert A.; Wysoki, Michael; Weiss, Jeffrey; Faro, Scott H.; Tsai, Fong Y. (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: The purpose of this study was to evaluate the presence of blood clots in femoral arterial sheaths maintained after cerebral angiography and the effect of heparinized saline on clot formation.METHODS: Twenty-three sheaths were evaluated in 18 patients. Sheaths were maintained for 14 to 80 hours (average, 33 hours; median, 24 hours). After the sheaths were removed, they were vigorously flushed with 60 mL of normal saline and the number and size of clots found in each sheath were recorded. Additionally, patients' age, catheter size, presence of heparin, amount of time the sheath was kept in the artery, and patients' coagulation status were recorded.RESULTS: Clots were found in 17 (74%) of the 23 sheaths. Ten catheters had continuous heparin drip, of which seven (70%) sustained clots. Of the 13 sheaths without heparin, 10 sustained clots (77%). The difference was not statistically significant. The average number of clots was 2.2, and the maximal length of clots ranged from 0.5 to 105 mm. No thromboembolic complications associated with sheath placement were encountered in our patient population.CONCLUSION: Blood clots are present in the vast majority of intraarterial sheaths maintained after cerebral angiography. These clots constitute a risk of thromboembolic complications in the event of repeat angiography. Sheath exchange should be considered before obtaining repeat cerebral angiograms.